2022
DOI: 10.1108/ci-12-2021-0245
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of interoperability factors on building information modelling (BIM) adoption in Malaysia

Abstract: Purpose Building information modelling (BIM) has transformed the traditional practices of the Architecture, Engineering and Construction (AEC) industry. BIM creates a collaborative digital representation of built environment data. Competitive advantage can be achieved with collaborative project delivery and rich information modelling. Despite the abundant benefits, BIM’s adoption in the AEC is susceptible to confrontation. A substantial impediment to BIM adoption often cited is data interoperability. Other fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 141 publications
(226 reference statements)
0
9
0
Order By: Relevance
“…Regarding the influence of compatibility, this study found that compatibility was not a significant influencing factor on the intention to adopt IFF among halal-certified companies in Malaysia. The findings are consistent with several studies that found an insignificant role of compatibility in adoption (e.g., Skafi et al, 2020;Ahmed et al, 2022;Parvand & Rasiah, 2022). One possible explanation could be that the owner-managers of halal-certified companies are less concerned about how IFF align with their practices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the influence of compatibility, this study found that compatibility was not a significant influencing factor on the intention to adopt IFF among halal-certified companies in Malaysia. The findings are consistent with several studies that found an insignificant role of compatibility in adoption (e.g., Skafi et al, 2020;Ahmed et al, 2022;Parvand & Rasiah, 2022). One possible explanation could be that the owner-managers of halal-certified companies are less concerned about how IFF align with their practices.…”
Section: Discussionsupporting
confidence: 91%
“…Top management support is a key factor that influences the innovation adoption in organisations. Wahab et al (2022) discovered that top management support positively influences the adoption of automated material handling equipment, while Ahmed et al (2022) indicated that top management shows its support and provides the necessary resources for the adoption of building information modelling. Therefore, the adoption intention of IFF relies mostly on top management support.…”
Section: Complexitymentioning
confidence: 99%
“…This leads to the normalization of attitudes of employees in an organization toward new technologies, work routines, and practices (Radhakrishnan et al, 2022). Therefore, when people start collecting information, dissipating and sharing about CT among their colleagues, and finding common ground with a predisposition for such applications, it influences organizational outcomes (Ahmed et al, 2022). Such individual perceptions and attitudes developed by individuals toward CT drive organizational capabilities that eventually become a type of intangible resource (Razzak, 2023; Uddin et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, when organizations deploy CT, it acts as an enabler that promotes harmony and collaboration among project members. Deployment of CT is likely to enhance the interactions between project workers and external entities, thus influencing factors related to individuals, organizations, and STF (Ahmed et al, 2022). Furthermore, based on the premise of RDT, when project workers deploy CT in their work, it will enhance the efficiency and effectiveness of interactions between them and their environment, thus leading to the development of positive effects on IF, OF, and STF.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Compared to other methods, SEM is a useful technique for assessing complex theoretical relationships among multiple variables [13], widely applied in the field of construction for technology adoption. Ahmed et al use partial least squares (PLS)-SEM in analyzing questionnaires distributed to 1200 construction companies to study the impact of interoperability-related factors, determinants, and barriers in adopting BIM technology in Malaysia's construction industry [14]. PLS-SEM is used by Al-Hashmy et al to investigate the impact of a computerized accounting information system (CAIS) on construction firm performance, finding that most of it is mediated by innovation [15].…”
Section: Introductionmentioning
confidence: 99%